How Does Long-Term Finance Affect Economic Volatility? - Demirguc-Kunt, Asli; Horváth, Bálint L.; Huizinga, Harry (World Bank, Washington, DC, 2016)
This paper examines how the ability to access long-term debt affects firm-level growth volatility. The analysis finds that firms in industries with stronger preference to use long-term finance relative to short-term finance experience lower growth volatility in countries with better-developed financial systems, as these firms may benefit from reduced refinancing risk. Institutions that facilitate the availability of credit information and contract enforcement mitigate the refinancing risk and therefore growth volatility associated with short-term financing. Increased availability of long-term finance reduces growth volatility in crisis as well as non-crisis periods.